Design and Evaluation of an Instructional Solar Energy Technologies Lab - Al-Addous, Mohammad; Class, Christina B. (International Journal of Online and Biomedical Engineering (iJOE), 2011)
This paper presents a design for a solar energy lab that allows students to plan, install and evaluate different system architectures and gain relevant practical experiences. The addressed learning outcomes are analyzed based on the 13 learning outcomes defined by the Accreditation Board for Engineering and Technology (ABET) as well as based on the taxonomy levels of the cognitive domain after Bloom. In this paper we present a sample lab assignment and map its tasks to the learning outcomes and cognitive domains. First results of qualitative student feedback are equally presented.